Reduction of greenhouse gas emissions using the endoscope with a light-emitting diode light source - Kikuchi, Katsuya; Yano, Tomonori; Hayashi, Yoshikazu; Ino, Yuji; Ueno, Takashi; Ozawa, Satoshi; Sugano, Kentaro (Endoscopy International Open, 2025)
Light-emitting diodes are being developed as a light source for an endoscope system instead of xenon lamps, contributing to improved diagnostic capability. This system also has the advantage of consuming less power than a conventional endoscope system using xenon lamps. Power consumption associated with endoscopy is an important factor in reducing greenhouse gas emissions. This study estimated the reduction in greenhouse gas emissions by using a light-emitting diode endoscope system.We calculated the power consumption and carbon dioxide emission reduction of the light-emitting diode endoscope system in comparison with a conventional endoscope system using a xenon light source. Calculations were based on actual data regarding operating time and the annual number of endoscopic procedures at Jichi Medical University Hospital. Estimates were also extended to a nationwide scale.If each type of endoscope system were used for all endoscopic procedures, the light-emitting diode endoscope system would reduce power consumption by 49% compared with the xenon endoscope system, resulting in a total power reduction of 838.7kWh, equivalent to 394.2 kg of carbon dioxide emissions. In Japan, the total power consumption would be reduced by 53%, corresponding to a total power reduction of 428,628.8 kWh, equivalent to 201,455.5 kg of carbon dioxide emissions.We estimated the effect of reducing carbon dioxide emissions using the light-emitting diode endoscope system. Wider adoption of the light-emitting diode endoscope system is expected to contribute to usefulness of endoscopic diagnosis and reduction in environmental impact.
Keywords: Endoscopy Upper GI Tract; Diagnosis and imaging (LCI, BLI, NBI); Endoscopy Lower GI Tract; Small bowel endoscopy